1996
DOI: 10.1111/j.1476-5381.1996.tb15602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein tyrosine kinase inhibitors on cytokine‐induced adhesion molecule expression by human umbilical vein endothelial cells

Abstract: . Endothelial cells can be stimulated by the pro‐inflammatory cytokines interleukin (IL)‐1α and tumour necrosis factor (TNF)α to express the leukocyte adhesion molecules E‐selectin, vascular cell adhesion molecule (VCAM)‐1 and intercellular adhesion molecule (ICAM)‐1 but the intracellular signalling mechanisms leading to this expression are incompletely understood. We have investigated the role of protein tyrosine kinases (PTK) in adhesion molecule expression by cytokine‐activated human umbilical vein endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 70 publications
6
38
0
Order By: Relevance
“…Thus, we have shown that thrombin, histamine or cytokines promote changes in the phosphotyrosine content of endogenous HUVEC proteins and that inhibitors of tyrosine kinases can attenuate distinct agonist-induced tyrosine phosphorylation events in parallel with PGIz release [2] or adhesion molecule expression [3]. One of the major tyrosine phosphorylated proteins observed in GPCA- [2] or cytokine-stimulated HUVEC [4] corresponds to the 42 kDa form of MAP kinase (p42 mapk) which is activated by phosphorylation on tyrosine and threonine residues catalysed by an upstream, dual-specificity MAP kinase kinase (MEK) [5]. In addition, there is a strong correlation between agonist-induced p42 mapk activation and some of the functional responses of HUVEC and we have hypothesised that activation of the MAP kinase cascade may be nec-*Corresponding author.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Thus, we have shown that thrombin, histamine or cytokines promote changes in the phosphotyrosine content of endogenous HUVEC proteins and that inhibitors of tyrosine kinases can attenuate distinct agonist-induced tyrosine phosphorylation events in parallel with PGIz release [2] or adhesion molecule expression [3]. One of the major tyrosine phosphorylated proteins observed in GPCA- [2] or cytokine-stimulated HUVEC [4] corresponds to the 42 kDa form of MAP kinase (p42 mapk) which is activated by phosphorylation on tyrosine and threonine residues catalysed by an upstream, dual-specificity MAP kinase kinase (MEK) [5]. In addition, there is a strong correlation between agonist-induced p42 mapk activation and some of the functional responses of HUVEC and we have hypothesised that activation of the MAP kinase cascade may be nec-*Corresponding author.…”
Section: Introductionmentioning
confidence: 94%
“…Agonist-induced expression of E-selectin was then assessed by enzyme-linked immunosorbent assay [3].…”
Section: Measurement Of E-selectin Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…JNK and p38 cascade participate in the control of IL-3 mRNA [21], and p38 cascade also participates in the induction of VCAM-1 expression by TNFa at human umbilical vein endothelial cells [11] and in the ICAM-1 expression of human pulmonary microvascular endothelial cells [10]. Also, there was a report that protein tyrosine kinase participates in the adhesion molecule expression of human umbilical vein endothelial cells by TNFa and IL-1a [22], but there have not been any reports on the signal transduction pathway of HDMEC ICAM-1 expression on HDMEC which is induced by AECA.…”
Section: Discussionmentioning
confidence: 99%